Assessing Financial Sustainability of Community Network Project through e3value Modelling and Simulation - WaiShiang, Cheah; XingZi, Chong; bin Khairuddin, Muhammad Asyraf; binti Jali, Nurfauza; Hidayat, Rahmat (Society of Visual Informatics, 2020)
Many efforts had been done to make ICTs available in rural area to increase their incomes and productivities. For example, a community ecommerce is introduced to promote community handicraft and income generation; other projects like deploying VSAT to improve the internet connectivity at rural area. Although the project is developed, it is facing a challenge like how to sustain the ICT4D projects? This paper presents the study of financial sustainability of community network project through e3value modelling and simulation. Â Financial sustainability is one of the important factor for community projects. As a NGO or researcher that is trying to help the community, is it possible for us to access the feasibility of any projects for communities so that a realistic suggestion or proposal can be planned? To sustain the community commerce, it cannot be denied that a well planning and measurement on financial sustainability of the projects is required. Hence, we believe that e3value can be used as a tool to measure the financial sustainability of community network projects. With the use of 3value model, it can serve as a reference for various parties in resolving the financial sustainability issue.